Flocculation, Pseudohyphal Development and Invasive Growth in Commercial Wine Yeast Strains - Carstens, Elsa; Lambrechts, M.G.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
Flocculation of Saccharomyces cerevisiae cells at the end of alcoholic fermentation is an important phenomenon in winemaking, especially in the production of bottle-fermented sparkling wine. Most wine yeast strains do not flocculate during the fermentation process and it is unknown whether they contain the necessary genes to flocculate and whether these genes are expressed adequately under wine-making conditions. These genes include the FLO1 flocculin gene which is one of the most important genes to confer the ability of yeast cells to flocculate and the MUC1 gene (subsequently also cloned as FLO11) encoding a mucin-Iike protein which was previously shown not only to play a key role in pseudohyphal development and invasive growth, but also to be involved in flocculation in S. cerevisiae.  Together with MUC1, the involvement of FL08 (encoding a transcriptional activator of FLO1) and TUPI in flocculation, pseudohyphal development and invasive growth indicates that these processes might somehow be linked. Therefore, in order to construct wine yeast strains that are able to flocculate, 25 commercial wine yeast strains were investigated for their ability to flocculate, form pseudohyphae and invade solid media.  Twenty-one of these strains were able to penetrate into agar media and different degrees of pseudohyphal and invasive growth were observed. The average length of cells and pseudohyphae and the efficiency of invasive growth varied among these strains. Two of the strains are known to flocculate in wine, while three other strains could be induced to aggregate to a limited degree in glycerol-ethanol medium. Southern blot analyses revealed the presence of homologous DNA sequences in all of the 25 strains using DNA fragments of FL08, MSS1O and MSS11 (encoding transcriptional activators of MUC1), FLO1 and MUC1 as probes. Using Northern blot analysis, FLO1 transcripts were detected in only one of the strains that showed constitutive flocculation in all the growth media tested.  MUCJ transcripts of varying sizes could be detected in most of the strains.  From these results it is clear that MUC1 does not primarily confer the phenotype of flocculation and that FLO1 (flocculation) and MUC1 (pseudohyphal differentiation, invasive growth and flocculation) are not co-regulated. We therefore suggest that MUC1, as opposed to FLO11, be retained as the most appropriate designation of this gene encoding the S. cerevisiae mucin-like protein.